“The Most Difficult ‘Job’ There Is” – Characteristics and Challenges of Unpaid Caregivers of Persons with Alzheimer’s and Related Dementias in Texas - Ronald Stokes-Walters; Calandra Jones; Mirela Ibrahimovic; Roxanne Alvarado-Torres; Lynda Taylor; Justin Buendia; Rachel Wiseman; Nimisha Bhakta (Journal of Long-Term Care, 2023)
Objective: To understand the conditions and impact on caregivers providing unpaid care to persons with Alzheimer’s disease or related dementias in Texas.